2022
DOI: 10.1186/s13690-022-00909-z
|View full text |Cite
|
Sign up to set email alerts
|

Organizing the health interview survey at the local level: design of a pilot study

Abstract: Background The local Health Interview Study (LHIS) was developed to gain health information at the level of the municipality in Flanders, the northern part of Belgium. It enables municipalities to make evidence-based decisions in their public health policy. To test the feasibility of implementing the LHIS, a pilot study was conducted in Melle, a small Flemish municipality with 11.736 inhabitants. Methods The target sample size was 1000 (≥ 15 years)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The outcomes of the COVID-19 health surveys in terms of the participation and sample composition indicated that certain subgroups of the population are easy to attract for survey research and remain interested for follow-up surveys whereas for other subgroups the opposite holds. Also in probability surveys not organized in COVID-19 context, participation rates differ by socio-demographic characteristics [ 18 , 56 ]. The large participation differences found in the COVID-19 health surveys made us think about using different recruitment approaches for different subgroups, especially for the youngsters.…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes of the COVID-19 health surveys in terms of the participation and sample composition indicated that certain subgroups of the population are easy to attract for survey research and remain interested for follow-up surveys whereas for other subgroups the opposite holds. Also in probability surveys not organized in COVID-19 context, participation rates differ by socio-demographic characteristics [ 18 , 56 ]. The large participation differences found in the COVID-19 health surveys made us think about using different recruitment approaches for different subgroups, especially for the youngsters.…”
Section: Discussionmentioning
confidence: 99%